Effect of eyedrops and applanation tonometry on optical biometry. Issue 6 (June 2021) - Nayer, Zacharia; Bhat, Amar; Sohal, Preet K.; Murdock, Braedon; Watson, Shelly H.; Belyea, David A.
Abstract : Phenylephrine, tropicamide, fluorescein–proparacaine eyedrops, and GAT did not significantly affect predicted postoperative refraction as measured by the Lenstar optical biometer. Abstract : Purpose: To determine whether eyedrops (phenylephrine, tropicamide, and fluorescein–proparacaine) and Goldmann applanation tonometry (GAT) have an effect on optical biometry measurements for preoperative cataract surgery workup. Setting: George Washington University, Washington, DC. Design: Nonrandomized controlled trial. Methods: Participants older than 18 years with no contraindications to eyedrops or tonometry were recruited. Optical biometry measurements were obtained on a single eye using the Lenstar LS900. One drop each of phenylephrine, tropicamide, and fluorescein–proparacaine was applied to the same eye, and measurements were repeated. GAT was performed, and measurements were repeated. For controls, the contralateral eye was also measured at each interval. Results: There was no statistically significant difference in mean predicted postoperative refraction (PPOR) keratometry (K) 1, K2, or axis postdrops and post-GAT 62 eyes (n = 62). After drops were applied, mean central corneal thickness increased from 540 to 542 µm ( P = .0002), mean anterior chamber depth (ACD) increased from 3.68 to 3.70 mm ( P < .0001), and lens thickness (LT) decreased from 3.66 to 3.65 ( P = .001). After GAT, ACD increased to 3.76 mm ( P < .0001), and LT increased to 3.60 mm ( P < .0001). There was no statistically significant difference in PPOR or other parameters for the control eyes (n = 5). Conclusions: GAT and phenylephrine, tropicamide, and fluorescein–proparacaine drops did not affect the primary outcome of PPOR. This suggests that cataract surgery candidates do not need to return for a separate preoperative visit for optical biometry.